The Effect of Underwriter Reputation, Auditor Reputation, and Leverage on Underpricing with Concentrated Ownership as A Moderation Variable - Afifah, Hasna Nur; rosidi, Rosidi; Farhan, Djuni (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to analyze: (1) the influence of underwriter reputation on the level of underpricing; (2) the influence of auditor reputation on the level of underpricing; (3) the effect of leverage on the level of underpricing; (4) the effect of ownership moderation is concentrated on the relationship between the reputation of the underwriter and the level of underpricing; (5) the effect of ownership moderation is concentrated on the relationship between auditor reputation and underpricing rates; (6) The effect of ownership moderation is concentrated on the relationship between leverage and underpricing levels. With the purposive sampling method, a sample of 363 IPO companies on the IDX in 2011-2021 was obtained. The analysis used was a moderated regression analysis, The hypothesis was tested using a t-test with a 5% alpa. The results of this study prove that: (1) the reputation of the underwriter has no effect on the value of underpricing; (2) auditor reputation has a significant negative effect on underpricing; (3) leverage has no effect on the underpricing value; (4) concentrated ownership is not a moderating variable between the underwriter reputation variable and underpricing; (5) concentrated ownership is not a moderating variable between the underwriter reputation variable and underpricing; (6) Concentrated ownership is not a moderating variable between the leverage variable and the underpricing